Asteroseismic Analysis of a Red Giant KIC 9145955 by Including the Small-scale Magnetic Fields in the Atmosphere - Yuetong Wang; Guifang Lin; Yan Li; Tao Wu; Yaguang Li (The Astrophysical Journal)
Recent convincing evidence is found within asteroseismology that suggests the magnetic fields exist in three red giants. Research on small-scale magnetic fields in the Sun and HD 49385 has shown that they have a certain corrective effect on the systematic discrepancies between observed and theoretical frequencies. Here we apply a similar method applied for the Sun to a red giant, KIC 9145955, to explore the impact of small-scale magnetic fields in the photosphere on its frequencies. We find that the calculated frequencies of our best-fit model, which simulates the effect of the magnetic fields by artificially modifying the Eddington T − τ relation, perfectly match those of the observed l = 0, 1, and 2 modes, indicating the existence of small-scale magnetic fields with an upper strength limit of 65 G and concentrating at a height 13,100 km in the photosphere. Based on the best-fit model, we revise the stellar parameters of KIC 9145955 as M  = 1.23 ± 0.04 M _⊙ , R  = 5.57 ± 0.06 R _⊙ , L  = 19.85 ± 0.5 L _⊙ , Age = 3.83 ± 0.5 Gyr, M _He  = 0.2108 ± 0.0005 M _⊙ , and R _He  = 0.0306 ± 0.0001 R _⊙ .